Left Impella®-device as bridge from cardiogenic shock with acute, severe mitral regurgitation to MitraClip®-procedure: a new option for critically ill patients. Issue 4 (2nd December 2020) - Vandenbriele, Christophe; Balthazar, Tim; Wilson, James; Adriaenssens, Tom; Davies, Simon; Droogne, Walter; Dubois, Christophe; Caetano, Ana Francisca; Goetschalckx, Kaatje; Jacobs, Steven; Janssens, Stefan; Ledot, Stephane; et al.
Abstract: Aims: Patients presenting with cardiogenic shock (CS) related to acute, severe mitral regurgitation (MR) are often considered too ill for immediate surgical intervention. Therefore, other less invasive techniques for haemodynamic stabilization should be explored. The purpose of this exploratory study was to investigate the feasibility and outcomes in patients with CS due to severe MR by using a novel approach combining haemodynamic stabilization with left Impella-support plus MR-reduction using MitraClip ® . Methods and results: We analysed whether a combined left Impella ® /MitraClip ® -procedure in a rare population of CS-patients with acute MR requiring mechanical ventilation is a feasible strategy to recovery in patients who had been declined cardiac surgery. Six INTERMACS-1 CS-patients with acute MR were studied at two tertiary cardiac intensive care units. The mean EURO-II score was 39 ± 19% and age 66.8 ± 4.9 years. All patients had an initial pulmonary capillary wedge pressure >20 mmHg and pulmonary oedema necessitating invasive ventilation. Cardiac output was severely impaired (left ventricular outflow tract velocity time index 9.8 ± 1.8 cm), requiring mechanical circulatory support (MCS) (Impella ® -CP; mean flow 2.9 ± 1.8 L per minute; mean support 9.7 ± 6.0 days). Despite MCS-guided unloading, weaning from ventilation failed due to persisting pulmonary oedema necessitating MR-reduction. In all cases, the severe MR was reduced to mild using percutaneous MitraClip ® -procedure, followed by successful weaning from invasive ventilation. Survival to discharge was 86%, with all surviving and rare readmission for heart failure at 6 months. Conclusions: A combined Impella ® /MitraClip ® -strategy appears a novel, feasible alternative for weaning CS-patients presenting with acute, severe MR. Upfront Impella ® -stabilization facilitates safe bridging to Mitraclip ® -procedure and the staged approach facilitates successful weaning from ventilatory support.